PERBANDINGAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN SIRSAK (Annona muricata L.) BERDASARKAN TEMPAT TUMBUH DENGAN METODE PEREDAMAN DPPH - Aminah Aminah; St Maryam; Muzakkir Baits; Ummi Kalsum (Faculty of Pharmacy, Universitas Muslim Indonesia, 2016)
Antioxidant activity assay has been conducted in order to determine the comparison of the antioxidant activity contained in the ethanol extract of the soursop leaves (Annona muricata L.) from Makassar, north Mamuju and Jeneponto. The amount of antioxidant activity obtained by testing against free radical DPPH (1,1-Diphenyl-2-picryl Hydrazyl) at concentrations of 10, 20, 30, 40 dan 50 ppm with 96% ethanol. The testing was done with the addition of 1 mL of the test solution with 4 mL DPPH 35 ppm. The absorbance of free radical activity was measured by UV-Vis spectrophotometer at the wavelength 515 nm and the IC50 value was calculated based on the absorbance data. The calculations showed that the soursop leaves from Makassar, North Mamuju, and Jeneponto had the IC50 value of 1.380 µg/mL, 1.512, and 1.420 respectively. The results showed that the samples came from Makassar had a higher antioxidant activity.